ChemInform Abstract: Iodine‐Catalyzed Radical Oxidative Annulation for the Construction of Dihydrofurans and Indolizines. Issue 40 (October 2015) - Tang, Shan; Liu, Kun; Long, Yue; Gao, Xinlong; Gao, Meng; Lei, Aiwen
Abstract The iodine‐catalytic system can be scaled up to 20 mmol with an excellent efficiency.